Efficacy of High-dose Steroids for Visual Acuity Improvement in Methanol-induced Toxic Optic Neuropathy - Theresia Yinski; Syntia Nusanti (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2018)
Introduction : Methanol-induced toxic optic neuropathy (TON) is defined as a visual impairment due to optic nerve damage by methanol poisoning. Not only is this disease entity underdiagnosed at times, this sudden blindness is also often diagnosed at a stage where recovery of vision is no longer possible. Materials and Methods : A literature search was conducted using PubMed, ClinicalKey, Google Scholar and ScienceDirect by combining the keywords ‘methanol’ or ‘methyl alcohol’, ‘intoxication’ or ‘poisoning’, ‘toxic optic neuropathy’, and ‘visual acuity’ with ‘high-dose steroid’. Results : The total amount of subjects in each article varied from 2 to 37, with mean age distribution of 26.34 to 55 years old, where most patients were male. The follow up duration varied from 1 week to 1 year. Four articles do not mention high-dose steroids treatment as therapy while the other four mention use of 1000 mg of intravenous methylprednisolone per day with divided doses of either 2x500 mg or 4x250 mg. Improvement percentages show 100% improvement in all studies that used high-dose steroids, while in the non-high-dose steroids studies the improvement percentages range from 33.33% to 90%. Summary : High-dose steroids are showing efficacy in improving visual acuity and reducing the inflammation in methanol-induced TON. The period of how fast the therapy takes effect is inconclusive, as the mean follow-up time differs widely per study. However, because most of the reviewed studies here are retrospective case series, a larger, more comprehensive study is required to acknowledge more of the efficacy profile.